Assessment of the Science, Technology and Innovation Integration Readiness in South Africa’s Government Departments - Raphasha, Idah Portia; Pouris, Anastassios (Information Research Communications, 2026)
Objectives This study assesses the extent to which Science, Technology and Innovation (STI) is integrated into the sectoral policy frameworks of South Africa’s 31 national government departments. Methodology Using quantitative policy document analysis, we examined 71 officially adopted departmental policy documents (1994–2024) and applied keyword frequency analysis to measure the visibility and salience of STI-related concepts. A Department of Science and Innovation (DSI) document was included only as a benchmark. Results Results show uneven and fragmented STI integration: roughly half of departments demonstrate moderate-to-high STI engagement, while the remainder show limited or negligible recognition of STI concepts. Traditional STI terms are more widely represented than emergent digital-related terms, such as the Fourth Industrial Revolution (4IR), which are confined to a small subset of departments. Conclusion These findings suggest that while STI is a recognised priority in some departments, comprehensive cross-government STI integration remains incomplete, indicating the need for stronger policy coordination and targeted efforts by the DSI to embed STI across sectoral strategies.
Keywords: Policy integration; Quantitative policy document analysis; Science; technology and innovation; South Africa.